Impact of low‐level pretransplant donor‐specific antibodies on outcomes after kidney transplantation. Issue 4 (18th August 2021) - Parajuli, Sandesh; Bath, Natalie M.; Hidalgo, Luis; Leverson, Glen; Garg, Neetika; R. Redfield, Robert; Mandelbrot, Didier A.
Abstract: Background: The effect of low‐level pretransplant donor‐specific antibody (DSA) on kidney transplant outcomes is not well described. The goal of this study was to compare outcomes among patients of varying immunologic risk, based on the level of pretransplant DSA. Methods: We retrospectively reviewed all adult kidney transplant recipients who had undergone a transplant at our center between January 2013 and May 2017. Patients were grouped as negative DSA (mean fluorescence intensity, [MFISUM  < 100]), low‐level DSA (MFISUM 100–1000), and positive DSA (MFISUM  > 1000). Rejection, infection, graft, and patient survival were outcomes measured. Results: Of 952 patients, 82.1% had negative DSA, 10.7% had low‐level DSA, and 7.1% had positive DSA. The positive DSA group had the highest rate of antibody‐mediated rejection (10.3%), followed by low‐level DSA (7.8%) and the negative DSA group (4.5%) ( p  = .034). The rate of BK viremia was highest in the positive DSA group (39.7%), followed by the low‐level group (30.4%) and the negative DSA group (25.6%), ( p  = .025). None of the other outcomes, including graft or patient survival, were different between the groups. Conclusion: While low‐level DSA should not prevent proceeding with kidney transplantation, it should not be ignored. Future studies are needed to investigate the long‐term effects of varying levels of pre‐transplant DSA on outcomes. Abstract : The presence of pretransplant donor‐specific antibody (DSA) represents a significant barrier to kidney transplantation for highly sensitized patients as they are less likely to undergo transplants compared with their nonsensitized counterparts. The goal of this study was to compare outcomes among patients of varying immunologic risk, based on the level of pre‐transplant DSA. The positive DSA group had the highest rate of antibody‐mediated rejection (10.3%), followed by low‐level DSA (7.8%) and the negative DSA group (4.5%) ( p  = .034). Also, the rate of BK viremia was highest in the positive DSA group (39.7%), followed by the low‐level group (30.4%) and the negative DSA group (25.6%), ( p  = .025).